ETHICS AND ACADEMIC INTEGRITY - NEW TEACHING MATERIALS FOR DOCTORAL STUDIES - Dan Vătăman (Romanian Journal of Historical Studies)
Following the entry into force of the Minister of National Education Order no. 3131/2018 on inclusion in education plans, for all university studies programs organized in higher education institutions in the national education system, of ethics and academic integrity courses, it was necessary to conceive and publish a set of didactic materials specially designed for doctoral students. As a result, I elaborated a university course that is accompanied by a seminar notebook, both teaching materials being designed to allow familiarizing of the doctoral students with the rules of ethics, deontology and integrity in academic activity and scientific research and thus developing a culture of responsibility in preventing, identifying and combating of potential academic frauds, especially plagiarism.